2003
DOI: 10.1086/375531
|View full text |Cite
|
Sign up to set email alerts
|

The Variable Jet of the Vela Pulsar

Abstract: Observations of the Vela pulsar-wind nebula (PWN) with the Chandra X-Ray Observatory have revealed a complex, variable PWN structure, including inner and outer arcs, a jet in the direction of the pulsar's proper motion, and a counterjet in the opposite direction, embedded in diffuse nebular emission. The jet consists of a bright, 8 00 long inner jet, between the pulsar and the outer arc, and a dim, curved outer jet that extends up to $100 00 in approximately the same direction. From the analysis of 13 Chandra … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
231
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(264 citation statements)
references
References 23 publications
31
231
0
Order By: Relevance
“…For instance, it could be a pulsar jet. Indeed, some pulsar jets are known to show extreme bending (e.g., the outer jet of the Vela pulsar; Pavlov et al 2003). The apparent lack of a similarly looking counterjet should not be surprising since the two jets can differ significantly both in shape and surface brightness due to the Doppler boost and/or proper motion effects (e.g., Pavlov et al 2003).…”
Section: Pwnmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it could be a pulsar jet. Indeed, some pulsar jets are known to show extreme bending (e.g., the outer jet of the Vela pulsar; Pavlov et al 2003). The apparent lack of a similarly looking counterjet should not be surprising since the two jets can differ significantly both in shape and surface brightness due to the Doppler boost and/or proper motion effects (e.g., Pavlov et al 2003).…”
Section: Pwnmentioning
confidence: 99%
“…Indeed, some pulsar jets are known to show extreme bending (e.g., the outer jet of the Vela pulsar; Pavlov et al 2003). The apparent lack of a similarly looking counterjet should not be surprising since the two jets can differ significantly both in shape and surface brightness due to the Doppler boost and/or proper motion effects (e.g., Pavlov et al 2003). On the other hand, the ratio of the compact PWN luminosity to that of the putative jet, L pwn1 /L pwn2 ∼ 5, is noticeably larger than that in the Vela and Crab PWNe but comparable to that of the PWN around PSR B1706-44 .…”
Section: Pwnmentioning
confidence: 99%
“…It is thought that the X-ray emission from CCOs is generally caused by the thermal cooling of the NS (e.g., Zavlin et al 1999), with typical temperatures of a few 10 6 K, as inferred from their thermal-like spectra. They have X-ray luminosities (L X ) in the range of 10 33 -10 34 erg s −1 and display X-ray spectra characterized by a black-body model with temperatures (kT ) in the range of 0.2-0.5 keV or a power-law model with very steep index Γ (see Pavlov et al 2003). Halpern & Gotthelf (2010) suggested that these objects could be weakly magnetized NSs (B ∼ 10 10 G), i.e., a kind of "anti-magnetars".…”
Section: The Nature Of Cxou J1703578-414302mentioning
confidence: 99%
“…To verify the other physical parameters of CXOU J170357.8-414302, we computed its L X and spin-down luminosityĖ, to compare with well-known CCOs objects (Pavlov et al 2003). Adopting again a mean distance of 14 kpc, we determined a total unabsorbed X-ray flux of F 0.7−2.0 = 6.9 × 10 −14 ergs cm −2 s −1 , which corresponds to an unabsorbed luminosity L X = 1.6 × 10 33 erg s −1 .…”
Section: The Nature Of Cxou J1703578-414302mentioning
confidence: 99%
“…For the jets in the Orion Nebula, it was also suggested that the bending may be caused by the ''rocket'' effect induced by the photoionizing UV radiation from nearby high-mass stars ; recent work by has investigated the influence of an ionizing photon flux on the jet-wind collision in the HH 555 jet. The presence of curved jets is also common to other environments, such as in active galactic nuclei, where they are observed as narrow-angleYtail radio sources (O'Dea & Owen 1986), or the pulsar jets in the Vela nebula, which are curved under the combined action of the wind within the supernova remnant and the proper motion of the pulsar (Pavlov et al 2003). Under a simplifying assumption the curvature of the jets can be described analytically (Begelman et al 1979;Canto & Raga 1995); however, these models cannot detail the shock structures and the intricate dynamics developing in the interaction and that were observed in a number of numerical studies.…”
Section: Introductionmentioning
confidence: 95%